Crisis, Confidence, and the Limits of Replication - Brown, Jeremy (Zygon, 2024)
There have been calls for a program of replication in the humanities. Although usually thought of as confined to the hard sciences, replication may, under the correct conditions, be a useful tool for historians who propose an explanation of why a set of events occurred. But the program of replication in the humanities is challenged when we consider degrees of freedom, i.e., the number of independent parameters that function within a system. Evidence from the sciences has revealed that experimental variables once thought of as unimportant might in fact be critical. Change just one of them and the experimental result changes in ways that were at first unimaginable. How then, are we to know if the degrees of freedom offered as part of a historical explanation are indeed satisfactory? There are constraints to what may be replicated, but this is the case for the sciences no less than for the humanities.